Плазмонные резонансы в металлических наноструктурах - Орлова, Д. А.; Бутенко, Н. С.; Стогний, Н. П. (ХНУРЭ, 2021)
Metallic nanostructures are of great importance in modern research both from the point of view of fundamental science and from the applied side. Interest has been observed precisely in recent years, which is caused by tremendous technological progress in the production of nanoscale structures. Along with passive plasmonic devices, there is growing interest in active systems that can be realized if the plasmonic nanostructure hybridizes with a material whose properties can be controlled over time.
Keywords: Плазмонный резонанс; наноструктура